2012
DOI: 10.1177/2047487312462146
|View full text |Cite
|
Sign up to set email alerts
|

Population attributable risk estimates for risk factors associated with hypertension in an Indian population

Abstract: Our results indicate that incident hypertension cases are largely attributable to the habit of tobacco use and alcohol consumption. Therefore, changing these selected lifestyle factors needs to be prioritized as a major strategy for reducing incidence of hypertension in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 24 publications
0
12
0
10
Order By: Relevance
“…The studies in north eastern States of India also reveal a high burden of hypertension in the adult population 8 9 10 11 . Such increase may be related to epidemiological transition involving dietary, lifestyle and behavioural changes added to genetic profile 12 . Children are also expected to be affected by these changes with probable increase in cardiovascular disease 13 .…”
mentioning
confidence: 99%
“…The studies in north eastern States of India also reveal a high burden of hypertension in the adult population 8 9 10 11 . Such increase may be related to epidemiological transition involving dietary, lifestyle and behavioural changes added to genetic profile 12 . Children are also expected to be affected by these changes with probable increase in cardiovascular disease 13 .…”
mentioning
confidence: 99%
“…Changing this male dominant culture is a cumbersome work but awareness for female's health and some separate policies for them could be useful in improving their health as well as decreasing the burden of diseases. However, Reddy, Prabhu (2005) and Shankarishan et al (2012) found more ratio with male subjects. 15,17 Logically, the male ratio in these studies may be the effect of participants.…”
Section: Gendermentioning
confidence: 72%
“…The Table 1 given below will show the quality assessed for all included studies. 15 Medium quality Manimunda et al, 2010 18 High quality Singh et al, 1997 21 Medium quality Singh et al, 2011 23 High quality Chaudhry et al, 2012 20 Medium quality Shankarishan et al, 2012 17 High quality Meshram et al, 2012 19 Medium quality Soudarssanane et al, 2008 14 Medium quality Sathish et al, 2012 29 High quality…”
Section: Quality Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies, both tobacco use (either smoking/chewing or both) and alcohol consumption were associated with an increased risk of hypertension [810]. We, in our previous study [11], have illustrated a dose-response relation between the number of cigarettes smoked per day ( χ 2 for trend = 26.07; P < 0.0001) and the amount of alcohol consumption per day ( χ 2 for trend = 24.26; P < 0.0001) and the risk of hypertension. The same study also calculated the population attributable risk (PAR) and were found to be 70.3% (95% CI 63.0–77.5) for tobacco use, 45.3% (95% CI 37.1–53.4) for tobacco chewing, 31.5% (95% CI 21.3–40.9) for smoking, and 33.6% (95% CI 22.9–44.4) for alcohol consumption.…”
Section: Introductionmentioning
confidence: 96%